"Too good" to succeed? Why not just try "good enough"! Some deliberations on the prospects of frugal innovations - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2013)
High-tech, German companies are facing a curious problem: their products are reportedly too good for the expanding global markets. So in a way they get penalised for offering a superlative quality. At a second glance, though, this doesn't seem surprising. For, succeeding in the emerging markets like India or China often requires developing market-specific products and services that enable an attractive value proposition without taking recourse to (excessive) over-engineering. Furthermore, the innovations should be able to cope with, and successfully circumvent, the given infrastructural restrictions ever so present in the rural and semi-urban areas in such economies.
urn:nbn:de:gbv:830-tubdok-12410
Keywords: 330